Analisis Teoritis Tren Work From Home di Era Digital: Kelebihan dan Kekurangan - Novianti, Lilis (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The COVID-19 pandemic of 2020 significantly altered various aspects of human life, including work dynamics. Work from home (WFH) emerged as a new and increasingly popular trend across various industries. WFH brings numerous benefits, such as increased productivity, cost efficiency, and enhanced quality of life for employees. However, it also poses several challenges, such as difficulties in coordination and communication, as well as the risk of burnout. This research aims to theoretically analyze the WFH trend in the digital era, focusing on the factors driving and hindering it, along with its implications for organizations and employees. The study employs a literature review method, gathering data from diverse sources, including scholarly journals, books, and online articles. The collected data are then descriptively analyzed to examine the WFH trend in the digital era. The research findings indicate that WFH trends have arisen due to advances in information technology, shifts in societal consumption patterns, and government policy support. Despite providing flexibility, this trend encounters challenges such as coordination and communication difficulties, burnout risks due to excessive workloads, and decreased employee productivity. The implications of these findings underscore the need for careful management strategies to maximize the benefits of WFH while addressing emerging obstacles.